ANALYSIS OF THE RELATIONSHIP BETWEEN FACTORS THAT INFLUENCE USER SATISFACTION IN GOJEK USING THE FUZZY DEMATEL METHOD - Putri, Elisa Ananda; Sari, Devni Prima (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Gojek is one of the most popular online transportation services in Indonesia. The success of Gojek is closely tied to user satisfaction. There are five factors influencing user satisfaction: service quality factor (A), price factor (B), ease of use factor (C), perceived benefit factor (D), and online servicescape factor (E). This research aims to identify which factors most significantly affect user satisfaction with Gojek services among students of the Mathematics Department at UNP. This study in applied research that is described using fuzzy DEMATEL and employs primary data obtained from questionnaire responses. The population of this study consists of students from the Mathematics Department at FMIPA UNP who enrolled in 2022, with a sample size of 75 students using the proportional random sampling technique. The results of this research indicate a significant relationship between the service quality factor (A) and price factor (B). With respective y coordinates of 0.583 and 2.074, the researcher can conclude that the price factor has the most significant influence on user satisfaction with Gojek among students of the Mathematics Department at FMIPA UNP in the 2022 cohort.